Touch in the helping professions : research, practice and ethics - Rovers, Martin W.; Malette, Judith, 1963-; Guirguis-Younger, Manal, 1967- (Health and society., 2017)
Inappropriate touch cases have sparked public outcry and made headlines, but a discussion on the importance and ethics of positive, caring, appropriate touch in the helping professions such as teaching, nursing and counselling is long overdue.